Bahasa Inggris EVALUASI GEOTEKNIK KELONGSORAN DENGAN PENDEKATAN ANALISIS BALIK PADA LERENG AREA DISPOSAL PIT 'X', TANJUNG ENIM, SUMATRA SELATAN - Gisa Nurputri Sugiawati; Raden Irvan Sophian; Muhammad Kurniawan Alfadli; Nur Khoirullah; Meilan Aditya Putra (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2025)
In open pit mining, the main activities include excavating the material from its original state and transporting it to the disposal area or stockpile, which forms an embankment. Slope stability in the disposal area should be monitored regularly to prevent losses caused by landslides. If a landslide occurs, it is important to identify the cause as a basis for recommending new slope design and implementing appropriate engineering measures to prevent future landslide occurrences. This study was conducted on a slope that had experienced a landslide in the Pit 'X' disposal area, Tanjung Enim, South Sumatra. This study aims to analyze the cause of the landslide by using a back analysis approach. Slope stability analysis was conducted using the Morgenstern-Price boundary equilibrium method, with failure probabilities calculated using Slide 2 software. Input data consisted of cohesion, internal friction angles, and unit weight of slope material. Based on the slope stability analysis, landslides occurred on slopes with a safety factor of 1 and a 40% probability of failure. This was caused by a 67.43% decrease in cohesion caused by the water-saturated condition of the clay material and the influence of the steep slope geometry. The proposed engineering solutions include slope grading, which increases the factor of safety by 30.31%, and the addition of counterweights, which further increases the factor of safety by 32.10%.